Gray versus yellow ventral coloration: Identity, distribution, color polymorphism and molecular relationships of the microhylid frog Platypelis mavomavo Andreone, Fenolio & Walvoord, 2003 - Rakotoarison, Andolalao; Scherz, Mark D.; Mullin, Katherine E.; Crottini, Angelica; Petzold, Alice; Ranjanaharisoa, Fiadanantsoa A.; Maheritafika, Hasina M. Rabe; Rafanoharana, James M.; Raherinjatovo, Henri; Andreone, Franco; Glaw, Frank; Vences, Miguel (Zootaxa, 2023)
The Malagasy frog Platypelis mavomavo from Ambolokopatrika in the North East of Madagascar was originally diagnosed based on its bright yellow venter, but only limited information on this species has become available after its initial description in 2003. Several Platypelis specimens with yellow ventral color have been erroneously assigned to this species due to a lack of DNA sequences from the P. mavomavo type series. On the other hand, the candidate species Platypelis sp. Ca10 from Andranomapanga in the Northern Central East of Madagascar with gray ventral color has been defined based on its genetic differentiation from other nominal Platypelis species. Here we study the genetic variation of P. mavomavo and P. sp. Ca10 based on mitochondrial (16S rRNA) and nuclear-encoded (RAG-1) genes, including a newly determined sequence from the P. mavomavo holotype, which was studied using a museomics approach. We find only limited genetic variation among the samples studied, and this variation is unlinked to ventral coloration but instead reflects geographic distribution. We, therefore, conclude that P. sp. Ca10 is a gray-colored variant of P. mavomavo, and that P. mavomavo is rather widespread in the North East and Northern Central East of Madagascar, with populations in areas bordering the North West (Ambohitantely) and Sambirano (Ampotsidy) geographic regions, and the yellow-bellied morph restricted to the North East (Makira, Ambolokopatrika). Due to the range extension of P. mavomavo, the conservation status of the species requires re-assessment.